2006
DOI: 10.1103/physrevd.73.024018
|View full text |Cite
|
Sign up to set email alerts
|

Cosmological expansion and the uniqueness of the gravitational action

Abstract: Modified theories of gravity have recently been studied by several authors as possibly viable alternatives to the cosmological concordance model. Such theories attempt to explain the accelerating expansion of the universe by changing the theory of gravity, instead of introducing dark energy. In particular, a class of models based on higher order curvature invariants, so-called f (R) gravity models, has drawn attention. In this letter we show that within this framework, the expansion history of the universe doe… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
161
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 121 publications
(165 citation statements)
references
References 29 publications
4
161
0
Order By: Relevance
“…The deviations peak at ∼ 10 −15 . Such deviations easily pass the stringent solar system tests of gravity from the Cassini mission [95] |γ − 1| < 2.3 × 10 −5 (63) under the assumption that the galactic field f Rg is given by the potential minimum. Models that saturate this observational bound have a sufficiently large |f Rg | that the thin-shell criterion is first satisfied at the edge of the Sun, where the fractional enclosed mass becomes 2M eff /3M tot ≈ 10 −5 (see Eqn.…”
Section: Solar System To Galaxymentioning
confidence: 99%
See 1 more Smart Citation
“…The deviations peak at ∼ 10 −15 . Such deviations easily pass the stringent solar system tests of gravity from the Cassini mission [95] |γ − 1| < 2.3 × 10 −5 (63) under the assumption that the galactic field f Rg is given by the potential minimum. Models that saturate this observational bound have a sufficiently large |f Rg | that the thin-shell criterion is first satisfied at the edge of the Sun, where the fractional enclosed mass becomes 2M eff /3M tot ≈ 10 −5 (see Eqn.…”
Section: Solar System To Galaxymentioning
confidence: 99%
“…What is less clear in the literature is whether any proposed metric-variation f (R) modification can simultaneously satisfy stringent solar-system bounds on deviations from general relativity as well as accelerate the expansion at late times [63,64,65,66,67,68,69,70,71,72,73,74]. Chiba [75] showed that the fundamental difficulty is that f (R) gravity introduces a scalar degree of freedom with the same coupling to matter as gravity that, at the background cosmological density, is extremely light.…”
Section: Introductionmentioning
confidence: 99%
“…(36) has been transformed to a first order nonlinear second kind Abel differential equation of the form dw/dθ = A(θ)w 3 +B(θ)w 2 [37]. As it is known from the theory of the Abel differential equations, an equation of this form has an exact solution if and only if the condition d [A(θ)/B(θ)] /dθ = kB(θ) is satisfied, where k is a constant [37].…”
Section: B First Order Corrections and General Properties Of λmentioning
confidence: 99%
“…For a static and spherically symmetric metric of the form given by Eq. (1), the field equations of the f (R) gravity in vacuum can be expressed as [29,36] …”
Section: Vacuum Field Equations In F (R) Gravitymentioning
confidence: 99%
“…[17] compose a subset of this class. It also has sufficient flexibility to bracket the behavior of models where the combination of a specific expansion history [18,19] and the Compton wavelength today fixes the form of f (R) [20]. For the ΛCDM expansion history and a dimensionless Compton wavelength parameter…”
Section: A Modelsmentioning
confidence: 99%